Peace Strengthens Human Prosperity: Islam and World Peace (American Journal of Islam and Society, 2010)
This conference, organized by the Faculty of Usuluddin at Sultan Sharif AliIslamic University (UNISSA), was held on 24-25 February 2010 at theRizqun International Hotel in Gadong, Brunei. The 119 local and 40 internationalparticipants presented 78 working papers. Local and internationalmedia outlets and representatives of government bodies, as well as officersfrom the Department of Community Development, the Ministry of ReligiousAffairs’ Syariah Affairs Department, and the Brunei Economic DevelopmentBoard, also attended. One of the main objectives was to clear upmisconceptions about Islam in order to bridge the gap and strengthen relationshipsand cooperation between Muslim and western countries.Abdul Muthalif Afuwardeen (conference co-chairman; dean, Facultyof Usuluddin, UNISSA) welcomed the audience and spoke of the importanceof religion and peace and how Islam and Muslims have been wronglyportrayed as symbols of terrorism, underdevelopment, and mockery. UstazHj Abdul Aziz Juned (state mufti) opened the event on behalf of SultanHas-sanal Bolkiah and urged participants to spread the truth about Islamworldwide. Keynote speaker Ismail Ibrahim (chariman of Islam Hadhari,National University of Malaysia), analyzed how many westerners considerIslam a religion of violence, war, and suppression due to their misunderstandingof jihad. He also called for mutual understanding among allparties ...